Monetary Policy Transmission and House Prices: European Cross Country Evidence - Kai Carstensen; Oliver Hülsewig; Timo Wollmershäuser (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper explores the importance of housing and mortgage market heterogeneity in 13 European countries for the transmission of monetary policy. We use a pooled VAR model which is estimated over the period 1995-2006 to generate impulse responses of key macroeconomic variables to a monetary policy shock. We split our sample of countries into two disjoint groups according to the impact of the monetary policy shock on real house prices. Our results suggest that in countries with a more pronounced reaction of real house prices the propagation of monetary policy shocks to macroeconomic variables is amplified.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C32; C33; E52; 330; Pooled VAR model; house prices; monetary policy transmission; country clusters; sign restrictions